Psychological and physical pain as predictors of suicide risk: evidence from clinical and neuroimaging findings. Issue 2 (March 2017) - Rizvi, Sakina J.; Iskric, Adam; Calati, Raffaella; Courtet, Philippe
Abstract : Purpose of review: Suicide is a multidimensional clinical phenomenon with complex biological, social and psychological risk factors. Therefore, it is imperative for studies to focus on developing a unified understanding of suicide risk that integrates current clinical and neurobiological findings. A recent line of research has implicated different classifications of pain in understanding suicide risk, including the concepts of psychache and pain tolerance. Although psychache is defined as the experience of unbearable psychological pain, pain tolerance refers to the greatest duration or intensity of painful stimuli that one is able to bear. This review will focus on integrating current clinical and neurobiological findings by which psychache and pain tolerance confer suicide risk. Recent findings: Results indicate that psychache has been identified as a significant risk factor for suicide and that psychache may be associated with the neurocircuitry involved in the modulation of physical pain. Converging evidence has also been found linking pain tolerance to self-injurious behaviours and suicide risk. The experience of psychache and physical pain in relation to other predictors of suicide, including reward processing, hopelessness and depression, are further discussed. Summary: Future research examining the pain-suicide connection is required to understand the mechanism behind clinically relevant risk factors for suicide, which can ultimately inform the construction of empirically supported suicide risk assessment and intervention techniques.